String Quintet in C major, op. 29, published by Artaria in 1802 or 1803 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Vienna; Austria; Artaria et Comp., 2023)
Earliest Viennese edition of the String Quintet in C major, op. 29, lacking plate no. and the composer's revisions, published by Artaria shortly after the appearance of the first edition issued by Breitkopf & Härtel in Leipzig